SEXUAL AFFILIATION OF THE MEN IN BYZANTIUM REFLECTED IN SYNTAGMA CANONUM WRITTEN BY MATTHEW BLASTARES (Annual of the Faculty of Philosophy in Skopje, 2015)
Syntagma Canonum written by Matthew Blastares is a collection of canonical and secular (civil) laws, collected and sorted by alpha-viten order published in Thessaloniki in 1335, and translated into Old Slavonic in 1347/48.Among the numerous regulations of criminal, family, inheritance and common law in Syntagma Canonum we can find a numerous regulations which are related to the sexual activities both of men and women. Here, in the paper that follows, will be processed and elaborated those provisions of Syntagma Canonum which are related to the men 's sexual activities, especially of those which were unusual (wrong), such as: Zoophilia, homosexuality, masturbation, those who have sinned in sleep and general infidelity (immorality), polygamy etc.
Keywords: LAW; ZOOPHILIA; HOMOSEXUALITY; MASTURBATION; POLYGAMY